The prediction of school achievement from a behavior genetic perspective: results from the german twin study on cognitive ability, self-reported motivation, and school achievement (CoSMoS) - Gottschling, Juliana; Spengler, Marion; Spinath, Birgit; Spinath, Frank M. (Personality and individual differences, 2012)
Much phenotypic research aims to identify which individual and familial characteristics explain individual differences in academic achievement. Behavior genetic studies can add informative value by analyzing the sources of this variation. The objective of the present study was to investigate the genetic and environmental origins of academic achievement and of two important and widely accepted predictors of school achievement, i.e. general cognitive ability (CA) and domain-specific self-perceived abilities (SPA). Results are based on cross-sectional data from the German twin study CoSMoS (97 MZ twin pairs, 183 DZ twin pairs; mean age 13.1years, SD=0.87). In line with previous research we confirmed the significance of genetic influences for all three variables, yielding heritability estimates between 30% and 62%. Multivariate genetic analyses further indicated that the genetic correlations between the variables were substantial and that SPAs in two school domains (German and Math) correlated with academic achievement for genetic rather than environmental reasons.
Gesehen am 17.04.2018